PENGARUH ION Cu2+, Zn2+, Cd2+, DAN Cr3+ TERHADAP PENYERAPAN LOGAM Pb2+ MENGGUNAKAN C-Sinamal Kaliks [4] Resorsinarena (CSKR) YANG DISINTESIS DARI MINYAK KAYU MANIS (Cinnamomum Burmanii) - Edi Nasra, Bahrizal, Faizah khairiyah, Sri Benti Etika, (Menara Ilmu, 2019)
Research on the effect of Cu2+, Zn2+, Cd2+, and Cr3+ ions as disturbing ions on the adsorption of Pb2+ metal using C-Cinamal Calix [4] Resorsinarena (CCCR) synthesized as an adsorbent using the batch method. The variables in this study were the types of disturbing ions namely Cu2+, Zn2+, Cd2+, and Cr3+ and the concentrations of each confounding ion which were 40 ppm, 80 ppm, 160 ppm, 240 ppm, and 400 ppm. The results showed a decrease in adsorption capacity of Pb2+ by synthesized CCCR. The addition of Cu2+, Zn2+, Cd2+, and Cr3+ ions to the adsorption of Pb2+ metal tends to disrupt at concentrations of 80 ppm, 160 ppm, 240 ppm and 400 ppm with a decrease in the percentage of adsorption of 17.736%, 49.289%, 86.111% and 67.986%. The main factor that influences the reduction in the percentage of Pb2+ adsorption by the synthesized CCCR caused by disturbing ions is that the ion radius level is also influenced by acid-base grouping according to the Hard and Soft Acids and Bases principle. Keywords --Adsorption, metal Pb, C-Cinamal Calix [4] Resorsinarena, Cinnamon Oil